Psychoanalysis and Affective Neuroscience. The Motivational/Emotional System of Aggression in Human Relations - Giacolini, Teodosio; Sabatello, Ugo (Frontiers in Psychology, 2019)
This article highlights the evolutionary biological epistemology in Freud psychoanalytic theory. The concepts of aggressive and sexual drives are cornerstones of the psychoanalytic epistemological system, concerning the motivational/emotional roots of mental functioning. These biological roots of mental functioning, especially with regard to aggressive drive, have gradually faded away from psychoanalytic epistemology, as we show in this article. Currently, however, Neurosciences, and in particular Affective Neuroscience (Panksepp, 1998), can help us to have a better understanding of the biological roots of human mental functioning. The motivational/emotional systems studied by Affective Neuroscience can give a new epistemological foundation to the aggressive drive concept in psychoanalytic theory. Over the course of human evolution, motivational/emotional systems have played a role in social relationships and also in mental functioning. In this regard, among the various types of aggression (ANGER in Panksepp taxonomy 1998) that we consider in our article, inter-male aggression, also named Dominance motivational/emotional system, is that which regulates social interactions between sexually matured adults. This type of aggression acts in complementary connection with FEAR motivational/emotional system that regulate submissive behavior and social defeat, and the latter one is of the more important stressors. The interaction between aggression and FEAR motivational/emotional systems gives rise to agonistic behavior or dominance/submission motivational/emotional system, as we propose in our article. There is now a large literature that identifies in the dynamic of Competitive behavior, which is one of the main factors of mental illness. When social interactions activate the competitive behavior, the subject can perceive himself as “destined to victory” or “destined to defeat,” activating either behaviors or emotions connected to the Involuntary Defeat Strategy or Involuntary Dominant Strategy (Sloman, 2002), which we can find in many types of mental disorders, for example, mood disorders or anxiety disorders.